Improve Surfaces properties of ABS Products fabricated by fused deposition modeling (FDM) 3D Printing: تحسين خواص الأسطح المصنعة عن طريق الطباعة ثلاثية الأبعاد بتقنية نمذجة ترسيب المنصهر FDM لمنتجات ABS - Suleiman Ibrahim Yousef, Mahmoud Al-Assad, Maher Al-Ibrahim (Journal of engineering sciences and information technology, 2019)
FDM (fused deposition modeling) 3D printing products often suffer from high surface roughness and low durability compared to conventional methods. In this paper, the effect of surface treatment after printing and coating with a layer of metal on its properties has been studied, The mechanical surface treatment methods (sandpaper) and chemical (solvent treatment) were compared and their effect on the adhesion strength of the deposited metal layer on the surface. The surface of the ABS product was coated with a layer of metal, the effect of both treatment and coating on the mechanical properties of printing products was studied. The results showed a clear decrease in surface roughness after surface treatment, where surface roughness decreased by 92%, and the best result was when grinding with sandpaper (2000 Grit) was Ra 0.35 μm. The tensile strength after acetone surface treatment was improved by 50% and after coating the product with a layer of metal by 56.25%. The adhesion test of the surface-deposited metal (CROSS-CUT) was conducted, and the result showed that the best adhesion durability was when the surface was treated with acetone vapor before coating.